Morphological awareness in readers of IsiXhosa - Rees, Siân Angharad (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2017)
This study focuses particularly on the development of four Morphological Awareness reading tests in isiXhosa and on the relationship of Morphological Awareness to reading success among 74 Grade 3 isiXhosa-speaking foundation-phase learners from three peri-urban schools. It explores in-depth why not all previously established Morphological Awareness tests for other languages suit the morphology of isiXhosa and how these tests have been revised in order to do so. Conventionally, the focus of Morphological Awareness literature has been on derivational morphology and reading comprehension. This study did not find significant correlations with comprehension, but rather with the children's ability to decode. Fluency and Morphological Awareness have not been given as much attention in the literature, but Morphological Awareness could be important for processing the agglutinating structure of the language in reading. This study also argues that it is not a specific awareness of derivational morphology over inflectional morphology, but rather a general awareness of one's language structure that is more important at this stage in their literacy development; specifically a general awareness of prefixes and suffixes. In addition, it was found that an explicit awareness of the morphological structure of the language related more to fluency and tests that accessed an innate and implicit Morphological Awareness had the strongest correlations overall with comprehension. The findings from this report have implications regarding how future curriculum developments for morphologically rich languages like isiXhosa should be approached. The positive and practical implications of including different types of Morphological Awareness tutoring in curricula is argued for, especially when teaching younger readers how to approach morphologically complex words in texts.
Keywords: Uncatalogued